Vibrational spectra of the α-MIIC2O4⋅2H2O oxalato complexes, with MII = Co, Ni, Zn - Wladimirsky, Alejandra (2011)
The infrared and Raman spectra of the α-MIIC2O4⋅2H2O oxalate complexes with MII = Co, Ni and Zn were recorded and briefly discussed on the basis of their structural peculiarities. The IR spectrum of a partially deuterated sample of α-ZnC2O4⋅2H2O is also discussed, reinforcing some of the performed assignments in the lower energy spectral region.